Zongmi on Chan - Broughton, Jeffrey L., 1944- (Translations from the Asian classics., 2009)
Japanese Zen often implies that textual learning (gakumon) in Buddhism and personal experience (taiken) in Zen are separate, but the career and writings of the Chinese Tang dynasty Chan master Guifeng Zongmi (780-841) undermine this division. For the first time in English, Jeffrey Broughton presents an annotated translation of Zongmi's magnum opus, the Chan Prolegomenon, along with translations of his Chan Letter and Chan Notes. The Chan Prolegomenon persuasively argues that Chan ""axiom realizations"" are identical to the teachings